A fibre optic oxygen sensor that detects rapid PO2 changes under simulated conditions of cyclical atelectasis in vitro - Formenti, Federico; Chen, Rongsheng; McPeak, Hanne; Matejovic, Martin; Farmery, Andrew D; Hahn, Clive E W (Respiratory physiology & neurobiology, 2014)
Two challenges in the management of Acute Respiratory Distress Syndrome are the difficulty in diagnosing cyclical atelectasis, and in individualising mechanical ventilation therapy in real-time. Commercial optical oxygen sensors can detect [Formula: see text] oscillations associated with cyclical atelectasis, but are not accurate at saturation levels below 90%, and contain a toxic fluorophore. We present a computer-controlled test rig, together with an in-house constructed ultra-rapid sensor to test the limitations of these sensors when exposed to rapidly changing [Formula: see text] in blood in vitro. We tested the sensors' responses to simulated respiratory rates between 10 and 60 breaths per minute. Our sensor was able to detect the whole amplitude of the imposed [Formula: see text] oscillations, even at the highest respiratory rate. We also examined our sensor's resistance to clot formation by continuous in vivo deployment in non-heparinised flowing animal blood for 24h, after which no adsorption of organic material on the sensor's surface was detectable by scanning electron microscopy.
Keywords: technologie optických vláken; Analysis of Variance; Animals; Pulmonary Atelectasis; atelektáza; počítačová simulace; Microscopy, Electron, Scanning; In Vitro Techniques; Fiber Optic Technology; biologické hodiny; Partial Pressure; Blood Coagulation; techniky in vitro; mikroskopie elektronová rastrovací; Optical sensor; krevní tlak; Computer Simulation; analýza rozptylu; Biological Clocks; parciální tlak; Oxygen; Cross-over computer control system; zvířata; Blood Pressure; hemokoagulace; kyslík; Cyclical atelectasis simulation